Measurements of Residual Stresses in Cold-Rolled 304 Stainless Steel Plates Using X-Ray Diffraction with Rietveld Refinement Method - P Parikin; P. Killen; A. Rafterry (PPIKSN-BATAN, 2009)
The determination of the residual stresses using X-ray powder diffraction in a series of cold-rolled 304 stainless steel plates, deforming 0, 34, 84, 152, 158, 175 and 196 % reduction in thickness has been carried out. The diffraction data were analyzed using the Rietveld structure refinement method. The analysis shows that for all specimens, the martensite particles are closely in compression and the austenite matrix is in tension. Both the martensite and austenite, for a sample reducing 34% in thickness (containing of about 1% martensite phase) the average lattice strains are anisotropic and decrease approximately exponential with an increase in the corresponding percent reduction (essentially phase content). It is shown that this feature can be qualitatively understood by taking into consideration the thermal expansion mismatch between the martensite and austenite grains. Also, for all cold-rolled stainless steel specimens, the diffraction peaks are broader than the unrolled one (instrumental resolution), indicating that the strains in these specimens are inhomogeneous. From an analysis of the refined peak shape parameters, the average root-mean square strain, which describes the distribution of the inhomogeneous strain field, was predicted. The average residual stresses in cold-rolled 304 stainless steel plates showed a combination effect of hydrostatic stresses of the martensite particles and the austenite matrix.Received: 14 March 2008; Revised: 13 October 2008; Accepted: 6 November 2008